Sleep Positioning By Levine’s Conservation Theory Approach Can optimize Enteral Nutrition In Low Birth Weight Infants (Jurnal Ilmu Kesehatan, 2021)
AbstractSleep Positioning by Levine’s Conservation Theory Approach Can Optimize Enteral Nutrition in Low Birth Weight Infants: Malnutrition which happens in the beginning period of life of low-birth-weight infants, will give long-term impact to cognitive, motoric, social-emotional, and behavioural function. The objective of this case study was to analyze the optimization of the fulfilment of enteral nutrition in low birth weight infants through sleep positioning with Levine’s Conservation Theory. The case study was conducted with five low-birth-weight infants that experienced enteral feeding intolerance. Nursing interventions were applied based on evidence-based nursing done by sleep positioning during the enteral feeding process. Levine’s Conservation Theory approach was applied by using principles of energy conservation, structural integrity conservation, personal integrity conservation, and social integrity conservation. Five cases were selected due to nursing problems in imbalanced nutrition: less than body requirements. The results showed that the implementation of sleep positioning with Levine’s Conservation Theory could reduce the incidence of desaturation, abdominal distension, and frequency of vomiting. Nurses can apply sleep positioning by Levine’s Conservation Theory approach as a standard of operational procedure in nursing intervention given to low-birth-weight infants that experience enteral feeding intolerance. Keyword: Enteral Feeding Intolerance, Levine’s Conservation Theory, Low-Birth-Weight Infants, Malnutrition, SleepPositioning